Moving HER2-low breast cancer predictive and prognostic data from clinical trials into the real world - Di Cosimo, Serena; La Rocca, Eliana; Ljevar, Silva; De Santis, Maria Carmen; Bini, Marta; Cappelletti, Vera; Valenti, Marta; Baili, Paolo; de Braud, Filippo G.; Folli, Secondo; Scaperrotta, Gianfranco; Volpi, Chiara; et al. (Frontiers in Molecular Biosciences, 2022)
Background - Previous data, mostly from clinical trials, reported that HER2-low status is associated with low pathological complete response (pCR), and favourable prognosis. Since these findings suggest the existence of an additional breast cancer subtype, we questioned if the predictive/prognostic value of HER2-low was also relevant in the real world. Methods - Data from non-metastatic breast cancer patients treated with neoadjuvant chemotherapy and surgery (2009-2020) were retrieved from our institutional prospectively-maintained registry. Univariable and multivariable logistic models were implemented to study the association between pCR and HER2 status. Univariable analysis of disease-free survival (DFS) was performed through Kaplan-Meier survival curves and log-rank tests. Results - Starting from a total of 790 consecutive cases, we identified 444 newly-diagnosed breast cancer patients featuring HER2 immunohistochemistry (IHC) 0 (HER2-0, n=109), and 1+ or IHC 2+/in situ hybridization negative (HER2-low, n=335) receiving anthracycline and taxane-based regimens in 88.9% of cases. Most of the patients were diagnosed with stage II (67.3%) and there was no difference of disease presentation according to HER2-status. pCR was attained by 71 (16.0%) patients and was significantly associated with increased DFS (p=0.031). Compared to HER2-0, HER2-low cases were more likely hormone receptor-positive (81.2% vs 43.1%, p< 0.001), well-differentiated (47.5% vs 26.6%, p= 0.001), less proliferative (21.5% vs 8.3%, p= 0.001) and less responsive to treatment (pCR 11.6% vs 29.4%, p< 0.0001). There was no difference in DFS according to HER2 status, though hormone-receptor (HR) negative/HER2-low cases tended to have a worse prognosis compared to HR-negative/HER2-0. By pCR achievement, DFS was 87.5.% (75.1- 100%) vs. 71.6% (65.9-77.8%) (p=0.161) in HER2-low and 89.1% (75.8-100%) vs. 72.1% (59.7-87.0%) (p=0.092) in HER2-0. Conclusion - Our real-world data show that HER2-low breast cancer patients represent roughly a half of the cases treated with neoadjuvant therapy, and have poor treatment response. In absence of pCR, HER2-low breast cancer patients have a dismal prognosis, especially when primary tumor hormone receptor status is negative. Studies are therefore needed to define the biology of these tumors for new therapeutic targets and to incorporate HER2-targeting agents in early-stage treatment.